Business performance for private higher education institutions in Malaysia - Ahmad, Hartini; Hashim, Fariza; Abu Bakar, Abdul Rahim; Md Isa, Filzah (Universiti Utara Malaysia, 2012)
In view of today’s development in the world economy, and globalization, Malaysia recognises that ‘knowledge’ is the passport to prosperity and social stability.The purpose of the study to identify the performance of Private Higher Education Institutions (IPTS) Malaysia based on each main factors, namely reputation, accreditation, admission, and finance.Initially, the failures Private Higher Education Institutions (IPTS) this could affect Malaysia's aspiration to become an education hub in the region.The interviews were conducted with personnel the senior and middle managers of the PHEIs, who are able to give the right information and related to the research questions by getting the data collection personally from the participants themselves.The important factors of these for business performance of the PHEIs, i.e. 1) clear and well defined mission, values and strategy; 2) top management and leadership style and support; 3) participation and total involvement that leads to performance; 4) transformation and change management; 5) human resource management; and 6) departmental integration and communication.